La inclusión digital en la educación: estrategias para reducir las brechas de habilidades digitales en estudiantes de la Escuela de Educación Básica “Provincia de Pichincha”. - Coyago Torres, Katherine Yessenia (2024)
The research titled “Digital Inclusion in Education: Strategies to Reduce the Digital Skills Gap in Students of the Basic Education School “Province of Pichincha” focuses on addressing digital inequality in a rural educational institution in the Gualaquiza canton. This work aims to identify and overcome the technological barriers that prevent students from developing essential digital skills for their academic performance and future professional life. The general objective of this research is to propose strategies to reduce the digital skills gap among students at the Basic Education School “Province of Pichincha.” To achieve this, a mixed methodology combining quantitative and qualitative approaches was used. Surveys were conducted with students, and interviews were held with teachers to gain a comprehensive view of the current digital competencies and technological needs of the educational community. The main results indicate a significant lack of basic digital competencies among the students, as well as insufficient technological infrastructure. Most students rely on smartphones for their academic activities, while access to computers and other devices is limited. Teachers, on the other hand, pointed out the lack of continuous training and technological resources as the main barriers to effectively integrating ICT into teaching. The conclusion of the research highlights the need to implement continuous training programs for teachers to ensure equitable access to technological resources. By addressing these areas, effective strategies can be developed to reduce digital gaps, promoting more inclusive and equitable education.